PENDEKATAN FIQH DAN PERATURAN PERUNDANG-UNDANGAN TERHADAP MAHAR DARI YOUTUBE ADSENSE - Muh Yassir Akbar Ramadhani (IAIN Palopo, 2022)
This research aim is to explore the legal standing of giving bride prices on income from youtube AdSense. Youtube AdSense is an unavoidable thing that refers to the development of the era and technological progress. Income that is from youtube Adsense no yet known whether halal or not also validity according to Indonesian Law. Because of that, the writer is motivated to discuss and present fiqh and the legislation that could reconstruct with income from youtube Adsense. The research method applied in this journal arrangement is qualitative with a state approach. The technique of data collection uses secondary sources from fiqh that as Alquran, hadith, and ijtihad. Also, Indonesian rules such as acts, the Compilation of Islamic Law, and government regulation. The result of this research is finding that as long as the bride approves the bride’s price on Youtube Adsense, the contract among Youtuber (groom) with Google is not opposed to Indonesia Civil Code, also content on Youtube accounts does not contain prohibited things, in the end, the bride price allowed.